Avicenna’s legacy and the modern model of public health: Transforming the roles of education and social justice - Dzhumaevna , Namazova Nodira (Goodwood Publishing, 2025)
Purpose: This study aims to develop an integrated model of societal health for the Bukhara region, synthesizing Abu Ali Ibn Sina’s (Avicenna’s) philosophical legacy with modern theories on the social and educational determinants of health. It explores how the quality of medical education, institutional equity, and psychosocial well-being interact to shape regional public health outcomes. Research Methodology: A quantitative mixed-methods design was employed, combining time-series data (2020–2024) from two medical universities with survey-based indicators of health literacy, preventive behavior, mental well-being, and equitable access. The Societal Health Index (SHI) was constructed and analyzed through econometric modeling using OLS and fixed-effects estimations with robust standard errors. Results: Findings indicate that a lower student–faculty ratio, higher academic qualifications, expanded clinical hours, and improved digital infrastructure significantly increase SHI scores. Institutional equity—measured through dormitory capacity, support services, and insurance coverage—also contributes positively to societal health. COVID-19 and youth unemployment exerted negative effects. Conclusions: The study confirms that educational and institutional quality jointly influence public health, aligning with Avicenna’s principles of moderation, mentorship, and justice. Integrating hard and soft skills within inclusive digital learning ecosystems strengthens the harmony between knowledge, equity, and well-being. Limitations: The short time span (2020–2024) and partial data aggregation may limit generalizability; future work should extend analysis to municipal and cross-regional levels. Contribution: This research bridges classical Avicennian philosophy with empirical public health modeling, offering an operational framework for policy alignment in education and healthcare modernization.